2017
DOI: 10.17507/jltr.0804.16
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Instruction Modalities Matter? Exploring the Influence of Concept Mapping and Translation Strategies Instruction on the Reading Comprehension Ability of Adult EFL Learners

Abstract: The present study was an attempt to compare the effect of concept mapping strategy instruction and translation strategy instruction on the reading comprehension ability of the Iranian EFL learners. To do so, 90 EFL learners at the intermediate level studying in a language institute in Ardabil, north Iran were randomly assigned into three equal groups (concept map, translation and control).  Having taken a reading pretest, the participants in experimental groups were instructed using mentioned strategies wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…There was also one case that did not specify the participants' level. Alkhateeb et al, 2015;Davaribina & Asl, 2017;Khajavi & Ketabi, 2012;Rassaei, 2019;Riahi & Pourdana, 2017;Soleimani & Nabizadeh, 2012 Senior high school students Hamedi et al, 2020;Kalhor & Shakibaei, 2012Liu et al, 2019;Tajeddin & Tabatabaei, 2016;Usman et al, 2017 Primary school students Chiang et al, 2016;Morfidi et al, 2018 Chiang et al, 2016;Liu, 2014;Liu et al, 2019…”
Section: Participantsmentioning
confidence: 99%
“…There was also one case that did not specify the participants' level. Alkhateeb et al, 2015;Davaribina & Asl, 2017;Khajavi & Ketabi, 2012;Rassaei, 2019;Riahi & Pourdana, 2017;Soleimani & Nabizadeh, 2012 Senior high school students Hamedi et al, 2020;Kalhor & Shakibaei, 2012Liu et al, 2019;Tajeddin & Tabatabaei, 2016;Usman et al, 2017 Primary school students Chiang et al, 2016;Morfidi et al, 2018 Chiang et al, 2016;Liu, 2014;Liu et al, 2019…”
Section: Participantsmentioning
confidence: 99%
“…Recent research has revealed the possibility of using translation as a pedagogical tool to benefit vocabulary building, wmorphosyntactic accuracy improvement, and intercultural awareness (Liashuk, 2018). Moreover, introducing translation strategies directly into L2 learning also helps to improve students' reading comprehension in L2 (Davaribina and Asl, 2017). As concluded by Popescu (2013), the application of translation activities into L2 learning roots in the inherent overlap in language competence, which allows for the interrelated improvement in linguistic knowledge, cognitive competence like planning, monitoring, and execution in reading and writing, as well as communicative abilities such as stylistic fluency, intercultural awareness (Cappelli, 2016;Navidinia et al, 2019).…”
Section: Translation Activities In the Development Of L2 Competencementioning
confidence: 99%
“…In skill-focused translation, translation is employed to target a given communicative skill or sub-skill. The main research object in this area is the impact of translation on learners' reading comprehension (Lee, 2013;Fatollahi, 2016;Davaribina & Asl, 2017). It was established that the introduction of sight translation tasks into regular reading comprehension practice results in a more significant increase in reading comprehension ability of Iranian sophomore students (Fatollahi, 2016).…”
Section: Skills-focused Translationmentioning
confidence: 99%
“…It was established that the introduction of sight translation tasks into regular reading comprehension practice results in a more significant increase in reading comprehension ability of Iranian sophomore students (Fatollahi, 2016). In a study by Davaribina and Asl (2017), translation of selected passages into L1 before completing a reading comprehension task improves reading comprehension ability of Iranian learners of English, demonstrating statistically significant difference from the performance of a control group. An additional issue to consider in this case is the fact that learners received explicit instruction on the basics of the translation strategies of equation, substitution, divergence, convergence, amplification, reduction, diffusion, condensation, and reordering.…”
Section: Skills-focused Translationmentioning
confidence: 99%
See 1 more Smart Citation